Fungicidal activity of a phospholipase A2-derived synthetic peptide variant against Candida albicans - Murillo, Luis A. (2007)
pEM-2, a 13-mer synthetic peptide variant derived from myotoxin II, a phospholipase A2 homologue present in Bothrops asper snake venom, has shown potent bactericidal activity in previous studies due to the combination of cationic and hydrophobic amino acids, including three tryptophan-substituted residues in its sequence. This study reports that pEM-2 also exerts potent fungicidal activity against a variety of clinically relevant Candida species, killing 100% of yeasts at concentrations near 10 mg/l (5 μM), as indicated by plate counting assays. Thus, this peptide displays a broad-spectrum antimicrobial activity, in the absence of hemolytic activity. The fungicidal action of pEM-2 against Candida can be partially inhibited by increasing concentrations of extracellular divalent cations (Ca+2 or Mg+2), in agreement with its proposed membrane- permeabilizing mechanism of action.